PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING BERBANTU MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN ADMINISTRASI TRANSAKSI KELAS XI BISNIS DIGITAL SMK N 6 MEDAN - Lasture Layani Silitonga; Muhammad Fitri Rahmadana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem addressed in this study is the low learning outcomes of students in the Transaction Administration subject for Grade XI Digital Business students at SMK Negeri 6 Medan. This is evidenced by the high number of students who failed to meet the Minimum Mastery Criteria (KKM), the lack of active student participation, and the continued use of conventional teaching methods. The purpose of this research is to determine the effect of the Inquiry Training learning model assisted by audiovisual media on the learning outcomes of students in the Transaction Administration subject. The study was conducted at SMK Negeri 6 Medan with a sample of 67 students, consisting of Grade XI Digital Business 2 as the experimental class and Grade XI Digital Business 1 as the control class. The sampling technique used was total sampling. Data collection was carried out using tests (pre-test and post-test). The validity of the test was measured using the Pearson Product Moment formula, and its reliability was calculated using the Kuder-Richardson Formula 20 (KR-20). The data analysis techniques used included t-tests and prerequisite tests such as normality and homogeneity tests, with the assistance of the SPSS version 23 software. The results of the independent t-test showed that there was a significant effect of the Inquiry Training learning model assisted by audiovisual media on the learning outcomes of students in the experimental class, with a significance value of 0.000 < 0.05. This proves that the Inquiry Training model assisted by audiovisual media is effective in improving student learning outcomes compared to conventional learning methods.